Sequence occurrence and structural uniqueness of a G-quadruplex in the human c-kit promoter - Todd, Alan K. (Oxford University Press, 2007)
The 22-nt c-kit87 promoter sequence is unique within the human genome. Its fold and tertiary structure have recently been determined by NMR methods [Phan,A.T., Kuryavyi,V., Burge,S., Neidle,S. and Patel,D.J. (2007) Structure of an unprecedented G-quadruplex scaffold in the c-kit promoter. J. Am. Chem. Soc., 129, 4386–4392], and does not have precedent among known DNA quadruplexes. We show here using bioinformatics and molecular dynamics simulations methods that (i) none of the closely related sequences (encompassing all nucleotides not involved in the maintenance of structural integrity) occur immediately upstream (<100 nt) of a transcription start site, and (ii) that all of these sequences correspond to the same stable tertiary structure. It is concluded that the c-kit87 tertiary structure may also be formed in a very small number of other loci in the human genome, but the likelihood of these playing a significant role in the expression of particular genes is very low. The c-kit87 quadruplex thus fulfils a fundamental criterion of a ‘good’ drug target, in that it possesses distinctive three-dimensional structural features that are only present in at most a handful of other genes.